Behavioural strategies of three wild-derived populations of the house mouse (Mus m. musculus and M. m. domesticus) in five standard tests of exploration and boldness: Searching for differences attributable to subspecies and commensalism - Frynta, Daniel; Kaftanová-Eliášová, Barbora; Žampachová, Barbora; Voráčková, Petra; Sádlová, Jovana; Landová, Eva (Behavioural processes, 2018)
Animal populations adopting a commensal way of life, e. g. house mice in buildings and stores, are subject to different selection pressures than those living in a non-commensal environment. This may radically influence their behaviour. This study investigated the effects of a commensal way of life on exploratory behaviour in mice. The focal population was non-commensal Mus musculus musculus from Northern Iran. To assess the effect of commensal way of life on exploratory behaviour, it was compared with commensal M. m. musculus from the Czech Republic and to assess the effect of subspecies, it was compared to non-commensal M. m. domesticus from Eastern Syria. We compared their behaviour in five tests of exploratory behaviour and boldness: an open field test with 1) free exploration and 2) forced exploration, 3) hole-board test, 4) test of vertical activity and 5) elevated plus maze. We detected a significant effect of population on behaviour in all five tests. M. m. domesticus was generally bolder and more active than M. m. musculus. Commensal mice were characterized by a higher level of vertical activity (climbing, rearing, jumping). These results suggest that the specific selection pressures of the commensal lifestyle select mice for higher affinity towards elevated places.
Keywords: Symbiosis; Animals, Wild; pohybová aktivita; Synanthropic; Exploration; Česká republika; pátrací chování; mužské pohlaví; Mice; House mouse; Czech Republic; Maze Learning; divoká zvířata; ženské pohlaví; zvířata; Exploratory Behavior; symbióza; Species Specificity; Boldness; myši; druhová specificita; Motor Activity; Female; bludiště - učení; Male; Animals